Studi Optimalisasi Perparkiran dan Pedestrian di Fakultas Teknik Jurusan Sipil Universitas Lampung - Nawawi, Sherly Novita Sari; Sulistyorini, Rahayu; Martono, Yohanes (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Faculty of Civil Engineering Department as one of the majors at the University of Lampung whichhas the number of students, faculty and others are quite large, this has resulted in demand forparking at the Faculty of Engineering Department of Civil is a problem that can not be ignoredbecause of the Faculty of Civil Engineering Department as a center of community activityacademic need a good arrangement and the campus community college population continues toincrease each academic year. This study aims to investigate the characteristics of the motorvehicle users both motorcycles and cars in the Faculty of Engineering Department of Civil,knowing parking needs in the Faculty of Engineering Department of Civil, find out if parking andpedestrian facilities in the Faculty of Engineering Department of Civil been sufficient,, analyzeparking management solution and pedestrian in the Faculty of Civil Engineering Department.Characteristics of motor vehicle users both motorcycles and cars derived from a comparisonbetween the accumulation of the highest parking vehicles with the number of parking spacesavailable, vehicle car I is 14 pieces of land, land second car that is 20 pieces, motorcycle land I is20 pieces, motorcycles land II is 27 pieces, motorcycles III, 11 pieces of land and land motorcycleIV is 4 pieces. Based on a survey and analysis parking requirements for the Faculty ofEngineering Department of Civil to cars I and II land at 192% / day, for the motorcycle land I of11.2% / day, for the motorcycle land II, III and IV of 126% / day .Keywords: Transportation, Parking, Pedestrian